Differences in late cardiovascular mortality following acute myocardial infarction in three major Asian ethnic groups. Issue 4 (December 2014) - de Carvalho, Leonardo P; Gao, Fei; Chen, Qifeng; Hartman, Mikael; Sim, Ling-Ling; Koh, Tian-Hai; Foo, David; Chin, Chee-Tang; Ong, Hean-Yee; Tong, Khim-Leng; Tan, Huay-Cheem; Yeo, Tiong-Cheng; et al.
Aim: the purpose of this study was to investigate differences in long-term mortality following acute myocardial infarction (AMI) in patients from three major ethnicities of Asia. Methods and results: We studied 15, 151 patients hospitalized for AMI with a median follow-up of 7.3 years (maximum 12 years) in six publicly-funded hospitals in Singapore from 2000–2005. Overall and cause-specific cardiovascular (CV) mortality until 2012 were compared among three major ethnic groups that represent large parts of Asia: Chinese, Malay and Indian. Relative survival of all three ethnic groups was compared with a contemporaneous background reference population using the relative survival ratio (RSR) method. The median global registry of acute coronary events score was highest among Chinese, followed by Malay and Indians: 144 (25th percentile 119, 75th percentile 173), 138 (115, 167), and 131 (109, 160), respectively, p <0.0001; similarly, in-hospital mortality was highest among Chinese (9.8%) followed by Malay (7.6%) and Indian (6.4%) patients. In contrast, 12-year overall and cause-specific CV mortality was highest among Malay (46.2 and 32.0%) followed by Chinese (43.0 and 27.0%) and Indian (35.9 and 25.2%) patients, p <0.0001. The five-year RSR was lowest among Malay (RSR 0.69) followed by Chinese (RSR 0.73) and Indian (RSR 0.79) patients, compared with a background reference population (RSR 1.00). Conclusions: We observed strong inter-Asian ethnic disparities in long-term mortality after AMI. Malay patients had the most discordant relationship between baseline risk and long-term mortality. Intensified interventions targeting Malay patients as a high-risk group are necessary to reduce disparities in long-term outcomes.